Analytical Review of Experience in the Development of Sustainable Finance and Prospects for Implementation in Kazakhstan - L. A. Kuanova; R. K. Sagiyeva; N. K. Zaitenova (Экономика: стратегия и практика)
The development of “sustainable” ﬁnance, that is, ﬁnancial instruments operating in the context of the implementation by companies of a set of environmental, social and governance principles (ESG principles), is gaining momentum in the main world markets. According to the Global Alliance for Sustainable Investments, these strategies already account for 35.9% of the total amount of invested assets. This trend is driven by a new global reality since the long-term development of the country and the company cannot be possible without resolving deepening environmental and social contradictions. In this regard, the purpose of this article is to develop recommendations acceptable to the practice of Kazakhstan based on the generalization of contemporary international experience in the development of various instruments of sustainable ﬁnance, as well as on studying institutional support measures for this process at the macroeconomic level.A review of the experience of several countries leading in the ﬁeld of environmentally and socially responsible investment demonstrates both general and speciﬁc features that can be successfully implemented in Kazakhstan, which is at the initial stage of this process. The research methodology is based on a comparative analysis of public policy, regulatory framework, and national speciﬁcs of the models of the six selected countries and regions. The obtained results have corresponding practical implications in terms of sustainable ﬁnance and ESG criteria-based investing regulation advancement in Kazakhstan by foreign practices adaptation.